From isonitriles to carbenes: synthesis of new NAC- and NHC-palladium(II) compounds and their catalytic activity - Hashmi, A. Stephen K.; Lothschütz, Christian; Böhling, Constantin; Rominger, Frank (Organometallics, 2011)
A series of NAC− and their structurally related NHC−palladium(II) isonitrile complexes, including examples of dinuclear complexes, were prepared. In a second series, NHC−palladium complexes bearing an aryl group on one nitrogen of the NHC ring and different cycloalkyl groups ranging from six- to 15-membered rings have been synthesized. The good yields document the value of the very short route to new palladium(II) NHC complexes. The stuctures have been investigated by crystal structure analyses of some representatives; in addition conformational studies by NMR were conducted. The reactivity in Suzuki cross-coupling reactions was investigated, showing turnover frequencies of up to 18 050 h−1 and a clear correlation of the size of the cycloalkyl moiety with the turnover number achieved for the coupling of chlorobenzene and 2,5-dimethylphenylboronic acid.
Gesehen am 31.08.2022